2017
DOI: 10.5812/gct.58383
|View full text |Cite
|
Sign up to set email alerts
|

High Fat Diet- Induced Neurotoxicity Alters Following vitamin E and C Administration in Hippocampus of Male Rats

Abstract: Background: Consumption of a high fat diet (HFD) leads to spatial memory impairment and hippocampal cell death. Objectives: The present study evaluated the capacity of antioxidant supplementation to interact with the effects of high fat diet at the molecular level. Methods: Animal groups were exposed to HFD for 9 months with free access to high fat diet and high fat diet with antioxidant supplementation (vitamin E, vitamin C, and Astaxanthin). At the end of the study, brains were removed and the level of brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
2
2
0
2
Order By: Relevance
“…Our results showed low levels of plasma NPY in restraint stress group given AT compared to control group I. A study conducted by Salehi et al 18 showe d similar results that used high fat diet to induce oxidative stress that was later ameliorated by administration of AT and AA in combination. In this study combination of two antioxidants was used because AA potentiates the action of AT when used in combination, by recycling the radical of AT to protect the cell membranes from lipid peroxidation caused by accumulation of ROS.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results showed low levels of plasma NPY in restraint stress group given AT compared to control group I. A study conducted by Salehi et al 18 showe d similar results that used high fat diet to induce oxidative stress that was later ameliorated by administration of AT and AA in combination. In this study combination of two antioxidants was used because AA potentiates the action of AT when used in combination, by recycling the radical of AT to protect the cell membranes from lipid peroxidation caused by accumulation of ROS.…”
Section: Discussionsupporting
confidence: 85%
“…Thereby antioxidants reduce neuronal toxicity by sparing action on neuronal cell membranes and secretion. 18 Similar results were noticed by Hounsom et al 19 who found depleted plasma NPY levels in rats deficient in alpha-tocopherol compared to control group. Another study conducted on mice given AT in fish oil showed improved cognitive functions and maintenance of NPY mRNA in the brain.…”
Section: Discussionsupporting
confidence: 78%
“…Supplementation using a combination of vitamin E and selenium decreased TBARS and improved the activity of antioxidative enzymes as well as the GSH level in the brains of rats poisoned with glucocorticoid [108]. A study conducted on rats receiving a high-fat diet for 9 months revealed impairment of spatial memory and increased mortality of hippocampal cells [172]. However, when such diet was enriched with the addition of vitamins C and E, a protective effect of the latter on nerve cells was observed [172].…”
Section: Vitamins and Provitaminsmentioning
confidence: 99%
“…A study conducted on rats receiving a high-fat diet for 9 months revealed impairment of spatial memory and increased mortality of hippocampal cells [172]. However, when such diet was enriched with the addition of vitamins C and E, a protective effect of the latter on nerve cells was observed [172].…”
Section: Vitamins and Provitaminsmentioning
confidence: 99%
“… (a) Kata et al, (b) Wang et al, (c) Ma et al, (d) Miedema et al, (e) Seker et al, (f) Kang et al, (g) Salehi et al, (i) Tanaka et al, (j) Husain et al …”
Section: Introductionunclassified